(Lessons and benefits for the dakwah extracted in the letter of Imam Malik Bin Anas to Imam Al-Layth Bin Sacd and the response of the latter)الدروس والفوائد الدعوية المستفادة من رسالة الإمام مالك بن أنس إلى الإمام الليث بن سعد ورده عليها - Ramdan Abdoslam A. Shahbana; Siti Ruqayah Tibek (Institut Kajian Rantau Asia Barat, 2012)
Most of intellectual treasures left behind by the scholars of the Ummah need to be studied in the light of dakwah as a benefit in serving the call to the religion of Allah Taala in everything bound with religious affairs. Of the treasures are letters and correspondences being exchanged among the scholars of the Ummah for the purposes of discussion, and exchanging opinions, viewpoints and orientations, and for the purposes of correcting mistakes and avoiding differences regarding some legal questions. The letters sent to the emirs and governors were for the purposes of avoiding injustices, restoring rights, correcting legal mistakes and so on. This study is concerned with the letter of Imam Malik bin Anas to Imam al-Layth bin Sacd and the response of Imam al-Layth bin Sacd. It is related to the dakwah, aimed at exploring benefits aspects of the letters in serving dakwah purpose. This study adopts qualitative and textual analysis in exploring and analyzing the contents of the two letters of words and other various matters or concerns in serving the dakwah and the callers. This study comes out with a collection of lessons and benefits on the dakwah that regarded as serving dakwah purpose and assisting the callers.